2020
DOI: 10.1021/jacs.0c07198
|View full text |Cite
|
Sign up to set email alerts
|

Dy3+ White Light Emission Can Be Finely Controlled by Tuning the First Coordination Sphere of Ga3+/Dy3+ Metallacrown Complexes

Abstract: Single lanthanide­(III) ion white light emission is in high demand since it provides the advantage of requiring only one chromophore for the control of the color. Herein, a series of Ga3+/Dy3+ metallacrowns (MCs) is presented, demonstrating outstanding white light colorimetric properties with CIE chromaticity coordinates of (0.309, 0.334) and correlated color temperature (CCT) equal to 6670 K for the MC emitting the closest to the standard white color. Experimental data reveal that the CIE coordinates within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…These are expected to generate distinct single-ion anisotropy and better magnetic isolation within the crystal lattice 81 – 83 . We decided to explore Dy(III) complexes which are yellow-to-white emissive as a result of the characteristic f-f electronic transitions 25 , 84 , and found to be highly anisotropic in diverse coordination environments.…”
Section: Introductionmentioning
confidence: 99%
“…These are expected to generate distinct single-ion anisotropy and better magnetic isolation within the crystal lattice 81 – 83 . We decided to explore Dy(III) complexes which are yellow-to-white emissive as a result of the characteristic f-f electronic transitions 25 , 84 , and found to be highly anisotropic in diverse coordination environments.…”
Section: Introductionmentioning
confidence: 99%
“…All these potential applications requires highly emissive materials and therefore the quest for new lanthanide-based coordination compounds exhibiting bright luminescence constitutes a continuous concern. [21][22][23][24][25][26][27][28] The strategy that consists on focusing on the choice of the ligand is, by far, the most commonly followed. [15][16][29][30] The works along this line have demonstrated that the ligands must present a structuring effect (via -stacking interactions, hydrogen-or halogen-bonds), an efficient antenna effect 31 and a good chemical affinity toward lanthanide ions.…”
Section: Introductionmentioning
confidence: 99%
“…The organic molecule N ,2-dihydroxybenzamide (H 2 dihybe) ( Scheme 1 A) incorporates a hydroxamate group in addition to the phenoxy group in the ortho-position and exhibits a rich coordination chemistry with many transition metals [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] with potential applications in various fields ranging from medicine [ 41 , 42 , 43 ] to materials [ 44 ], and physical sciences [ 40 , 45 ].…”
Section: Introductionmentioning
confidence: 99%